Efektivitas Pengendalian Internal dalam Mencegah Pembiayaan Macet pada BMT Al-Hijrah Bukittinggi - Rahayu, Firly Gusti; Kenedi, Jon (Al-DYAS, 2024)
This research aims to examine the process of internal control policies in preventing bad financing at BMT Al-Hijrah Bukittinggi and to analyze the effectiveness of internal control in preventing bad financing at BMT Al-Hijrah Bukittinggi. The type of research used is qualitative research. The analysis techniques used are interview techniques, observation techniques, and documentation techniques. Bad financing is caused by payments that are not on time or not paying arrears that have been previously agreed. There are two causal factors, namely internal and external factors. The internal factor is the lack of supervision and checking carried out by BMT Al-Hijrah Bukittingi and forgetting to check receivables. Meanwhile, external factors are caused by customers and also not paying attention to the 5C principles when analyzing financing for prospective customers, resulting in bad financing.